Age-related macular degeneration: an overview and update. Issue 3 (May 2006) - Lip, PL; Menon, VJK
Age-related macular degeneration affects a growing number of patients in the elderly population every year, with a profound effect on their lifestyle as a result of visual disability. Visual rehabilitation plays a key role in maximizing patients' remaining vision, confidence and independence. In recent years, there has been a tremendous advance in treatment for wet age-related macular degeneration, and an even wider range of antiangiogenic agents should be available to improve disease prognosis in the near future. This paper also gives an overview of the natural course of age-related macular degeneration, its diagnosis, investigations and past/present treatment options.